Geometrical Effects in the Surface Plasma Spraying Process on the Surface - A.S. Dolgov; A.L. Lorent (Журнал нано- та електронної фізики)
Influence of the widespread geometrical detail singularities and particle flux on the deposition efficiency is considered and the corresponding advices are made. The expression of deposition on a surface unit at constant surface element rotation frequency is determined on the basis of approximated scheme with negative curvature. The deposition values are resulted for different types of curvature. The value of the particle flux divergence in the capacity of compensative factor for the curvature deposition inhomogeneity is considered. The fact that the strong dependence of the deposition probability on the bombarding angle leads to the reduction of the general level of deposition for different schemes is revealed.